Agama islam sebagai obyek dan gejala sosial budaya dalam kajian ilmiah (sebuah refleksi kajian filosofis studi islam) - Zuhri, Ahmad Minan (Majelis Pembinaan Kader Sumber Daya Insani Pimpinan Daerah Muhammadiyah Kota Salatiga, 2021)
This paper seeks to provide insight that the emergence of Islam has a very large influence on aspects of people's lives. Historically, Islam has become an object that gives a new color to people's lives, giving rise to symptoms that can change the order of life. Social and cultural aspects are the focus of discussion in this article in order to focus on a comprehensive discussion. The method used in this study uses a qualitative approach to literature study by comprehensively analyzing studies related to philosophical studies of Islamic studies. The results show that all the commands in the Qur'an that are carried out by Muslims have a very large influence on the social and cultural communities that exist in society. Keywords: Islam, Socio-cultural Symptoms, Scientific Studies